2015
DOI: 10.1080/09168451.2015.1039481
|View full text |Cite
|
Sign up to set email alerts
|

Carbon tetrachloride-induced hepatic and renal damages in rat: inhibitory effects of cacao polyphenol

Abstract: Here, we investigated the protective effect of cacao polyphenol extract (CPE) on carbon tetrachloride (CCl4)-induced hepato-renal oxidative stress in rats. Rats were administered CPE for 7 days and then received intraperitoneal injection of CCl4. Two hours after injection, we found that CCl4 treatment significantly increased biochemical injury markers, lipid peroxides (phosphatidylcholine hydroperoxide (PCOOH) and malondialdehyde (MDA)) and decreased glutathione peroxidase activity in kidney rather than liver,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 34 publications
(29 reference statements)
4
9
0
Order By: Relevance
“…This study reports for the first time the hepatoprotective effect of UNCP against A/L-induced hepatic damage in guinea pigs. Similar effect of UNCP has been demonstrated in other studies where it was shown that UNCP reduced liver damage in mice infected with Plasmodium berghei [ 59 ], prevented alcohol-induced hepatic damage in rats [ 60 ], and protected against liver and renal damage by carbon tetrachloride [ 61 ].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This study reports for the first time the hepatoprotective effect of UNCP against A/L-induced hepatic damage in guinea pigs. Similar effect of UNCP has been demonstrated in other studies where it was shown that UNCP reduced liver damage in mice infected with Plasmodium berghei [ 59 ], prevented alcohol-induced hepatic damage in rats [ 60 ], and protected against liver and renal damage by carbon tetrachloride [ 61 ].…”
Section: Discussionsupporting
confidence: 81%
“…Cocoa increases nitric oxide levels in humans as observed for studies involving consumption for flavonoid rich chocolate and cocoa drinks [ 62 , 63 ]. Superoxides and peroxides have been found to scavenge nitric oxide [ 61 ]. The rise in nitric oxide caused by A/L observed in the present study may be consistent with others who have suggested that to be as a result of a compensatory mechanism trying to restore the nitric oxide level [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bile duct ligation causes acute and chronic renal ( 92 ) and cardiac dysfunction ( 93 ). Administration of carbon tetrachloride (CCl 4 ) is a model of acute (or if repeated, chronic) hepatic failure causing widespread disruption to cardiac and renal function, although CCl 4 generates oxidant injury directly in other organs ( 94 ). Other relevant experimental models include toxin induced murine models, as well as some murine models of autoimmune hepatitis and primary biliary cirrhosis ( 95 ).…”
Section: Cardiac and Renal Involvement In Systemic Disease (Type 5 Crmentioning
confidence: 99%
“…Therefore, we speculated that flavonoids might be active compounds that can reduce the impact of liver-damaging substances by inhibiting the expression of CYP2E1, which might be one of the hepatoprotective mechanisms of flavonoids. Also, an investigation of the effects of flavonoids on CYP2E1 expression is necessary since some daily foods (purple potato, purple sweet potato, broccoli, bitter gourd, garlic, and tomato), beverages (coffee and cacao polyphenol), and drugs ( Schisandra chinensis , danshen, Gelsemium elegans , isoniazid, diallyl sulfide, sulforaphane, and tamoxifen) are metabolized by CYP2E1 (Vang et al, 1991; Gu et al, 1992; Wargovich, 2006; Wang et al, 2010, 2015; Konstandi et al, 2013; Su et al, 2013; Ahmad et al, 2014; Lu et al, 2014; Zhou et al, 2014, 2015; Shayakhmetova et al, 2015; Suzuki et al, 2015; Jiang et al, 2016a,b). …”
Section: Introductionmentioning
confidence: 99%